Fire does not change sprouting nor flowering, but affects fruiting phenology in a Neotropical savanna community - Valentin-Silva, Adriano [UNESP]; Alves, Vinícius Nunes [UNESP]; Tunes, Priscila [UNESP]; Guimarães, Elza [UNESP] (Elsevier, 2021)
In fire-prone ecosystems, such as savannas, fire has been a common event for thousands of years. In these biomes, phenology is a functional trait characterizing the responses of plant communities to fire. In this study, we aimed to evaluate the effects of fire on the period of occurrence, seasonality, and number of species expressing vegetative and reproductive phenophases (sprouting, flowering, and fruiting) in a South American savanna community. We burned experimental plots in 2013, and during the subsequent year, we performed monthly evaluations of the presence and absence of vegetative and reproductive structures in 44 species of angiosperms in the control and burned plots. We described plant phenology at two levels: (i) considering all sampled plant species together (community); and (ii) separately considering the species found in the herbaceous-subshrub and shrub-tree layers (vegetation strata). We analyzed the data using circular statistics and generalized linear mixed models. At the community level, fire did not alter the mean period of occurrence of vegetative and reproductive phenophases; however, we observed changes in fruiting seasonality, which were mainly caused by the changes occurring in the shrub-tree layer. Except for those found in the shrub-tree layer, more species expressed the analyzed phenophases after fire compared to the “control” treatment. This study provides information regarding the responses of plants to burning at the end of the dry season, when most anthropogenic fires occur. Additionally, according to climate change predictions, the Southern Hemisphere is expected to experience longer dry seasons, which may contribute to an increased frequency of anthropogenic fires. Therefore, this phenological information can motivate subsidies that are important for the conservation of this biome and management plans related to the prescription of fires.
Keywords: Cerrado; Flowering; Fruiting; Savanna; Seasonality; Sprouting